2021
DOI: 10.1364/ol.428238
|View full text |Cite
|
Sign up to set email alerts
|

Temporal differentiation and integration of few-cycle pulses by ultrathin metallic films

Abstract: We study theoretically the temporal transformations of few-cycle pulses upon linear interaction with ultrathin metallic films. We show that under certain conditions on the film thickness and the pulse spectrum, one obtains the temporal differentiation of the pulse shape in transmission and the temporal integration in reflection. In contrast to previous studies, these transformations are obtained for the field of few-cycle pulses itself instead of the slowly varying pulse envelope. These results open up new opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…The coherent interaction of ESP with resonant media leads to the appearance of a number of new and unusual phenomena during the propagation of such pulses in resonant media. In particular, this is the possibility of integrating and differentiating the temporal form of the pulse field strength, and not their envelope [24]. The possibility of compression of single-cycle bipolar pulses in a two-level medium due to the attraction of their unipolar components propagating coherently in the self-induced transparency mode (SIT) in a resonant medium was shown in [25].…”
Section: Introductionmentioning
confidence: 99%
“…The coherent interaction of ESP with resonant media leads to the appearance of a number of new and unusual phenomena during the propagation of such pulses in resonant media. In particular, this is the possibility of integrating and differentiating the temporal form of the pulse field strength, and not their envelope [24]. The possibility of compression of single-cycle bipolar pulses in a two-level medium due to the attraction of their unipolar components propagating coherently in the self-induced transparency mode (SIT) in a resonant medium was shown in [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent paper of Pakhomov et al [54], it was demonstrated that the propagation of few-and subcycle pulses through nanometer-thick metallic films can result in efficient temporal differentiation and integration of the pulses. Namely, under certain restrictions on the pulse spectrum and the film thickness the pulse reflected from the film has the shape of the temporal integral of the incident pulse, while the pulse transmitted through the film can have the shape of the temporal derivative of the incident pulse.…”
Section: Shaping Of Quasi-unipolar Pulsesmentioning
confidence: 99%
“…Obtaining such UPs is possible, for example, by integrating and differentiating the time form of the field strength in thin metal films [38,39]. Experimentally, rectangular UPs in the THz frequency range in the form of precursors in an electro-optical crystal were obtained quite recently [19], and the possibility of obtaining rectangular terahertz unipolar pulses by excitation of a metal film was theoretically shown [20] using femtosecond laser pulse.…”
Section: Introductionmentioning
confidence: 99%